High-resolution Magnesium/Calcium ratios from IODP Site 342-U1403, Newfoundland Margin - Alexa Fischer; Sietske J Batenburg; André Bahr; Silke Voigt; Anne Rheinberger; Sarah Schmickal; Silvia Rheinberger; Markus Greule; Stefan Rheinberger; Oliver Friedrich (PANGAEA, 2025)
This dataset lists the results of the Mg/Ca measurements (in mmol/mol) from International Ocean Discovery Program (IODP) Site U1403 off Newfoundland (~40°N, 51°W; 4944 m water depth, Expedition 342, NW Atlantic Ocean). Mg/Ca analysis were carried out on specimens of N. truempyi. Mg/Ca values were analyzed using a Agilent Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) 720. Mg/Ca data was normalised relative to the ECRM752-1 standard.